2011
DOI: 10.1200/jco.2010.29.2235
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Pneumonitis in Patients With Advanced Renal Cell Carcinoma Treated With Temsirolimus

Abstract: Patients with ARCC receiving temsirolimus should be monitored closely for development of pneumonitis, and their management should be altered if clinical symptoms appear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 24 publications
7
64
4
1
Order By: Relevance
“…A retrospective blinded review of chest computerized tomography (CT) images in the ARCC phase III trial indicated that 29% of patients treated with temsirolimus developed temsirolimus-related pneumonitis [Maroto et al 2011]. This incidence is similar to that reported in other retrospective radiographic analyses of patients treated with TOR inhibitors and confirms that pneumonitis is a class-effect toxicity of mTOR inhibitors.…”
Section: Clinical Presentation and Management Of Side Effects Relatedsupporting
confidence: 66%
“…A retrospective blinded review of chest computerized tomography (CT) images in the ARCC phase III trial indicated that 29% of patients treated with temsirolimus developed temsirolimus-related pneumonitis [Maroto et al 2011]. This incidence is similar to that reported in other retrospective radiographic analyses of patients treated with TOR inhibitors and confirms that pneumonitis is a class-effect toxicity of mTOR inhibitors.…”
Section: Clinical Presentation and Management Of Side Effects Relatedsupporting
confidence: 66%
“…In the global ARCC Phase III trial, treatment-related pneumonitis was reported in 2% of patients receiving temsirolimus (13). A retrospective analysis of the global ARCC trial showed that 29% (52 of 178 evaluable patients) developed radiographically identified drug-related pneumonitis (20). In our study, treatment-related ILD was reported in 17% (14 patients) and was the most frequent cause of treatment discontinuation or dose modification.…”
Section: Discussionmentioning
confidence: 78%
“…Often called interstitial pulmonary fibrosis, ILD is characterized by chronic inflammation and progressive fibrosis of the pulmonary interstitium. A very high frequency of patients (up to 36%) treated with rapalogs were found to have radiographic evidence of ILD, but the pathology often regressed upon discontinuation of mTORtargeted treatment (29)(30)(31)(32)(33)(34)(35). Interestingly, there is mounting evidence that aberrant activation of EMT could contribute to pulmonary fibrosis through the transdifferentiation of alveolar epithelial cells into proliferating fibroblasts (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%